(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
This study investigates the antioxidant and cytotoxic effects of 2-(3,4-dimethoxyphenyl)-3-(4-fluorophenyl)-5,7-dimethoxy-4H-chromen-4-one (compound A), a derivative of rutin, a well-known flavonoid with antioxidant properties. The antioxidant activity of compound A was evaluated using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay, while its cytotoxic effects were assessed using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay on Hep-G2 cells, a human liver cancer cell line.In the DPPH assay, compound A demonstrated dose-dependent antioxidant activity, with increasing concentrations leading to higher percentage inhibition of DPPH radicals. At concentrations ranging from 15 to 240 mg/ml, compound A exhibited significant antioxidant effects, with percentage inhibition values ranging from 10% to 70%. These results suggest that compound A possesses potent antioxidant properties, which could be attributed to its structural similarity to rutin.Conversely, in the MTT assay, compound A displayed dose-dependent cytotoxic effects on Hep-G2 cells. At lower concentrations (15-60 mg/ml), compound A induced cell death, as evidenced by low percentage cell viability values ranging from 4% to 22%. However, at higher concentrations (120-240 mg/ml), compound A promoted cell survival, with percentage viability values increasing up to 52%. This biphasic effect suggests that compound A exhibits both cytotoxic and cytoprotective effects on Hep-G2 cells, depending on the concentration range.Overall, our findings indicate that compound A possesses dual antioxidant and cytotoxic properties, making it a promising candidate for further investigation as a potential therapeutic agent against oxidative stress-related diseases and cancer. Further studies are warranted to elucidate the underlying mechanisms of action and to evaluate the efficacy and safety of compound A in preclinical and clinical settings.